Economic Assessment of Fattening Beef Cattle Through The Rice Straw Utilization - Priyanti, Atien; Kostaman, T; Haryanto, B; Diwyanto, K (Indonesian Bulletin of Animal and Veterinary Sciences, 2001)
Based on the agricultural production, Indonesia has very high potential to increase rice production through the implementation of adapted and liable technology. The role of non-rice sub sector is also needed to harmonize management in various aspects, in which one of them is livestock sub sector. This management could be done through the development of livestock farming using the rice straw as one of the potential animal feed. The objective of the study was to get a conceptual integrated systems of rice production based on livestock (cattle) development. The estimation of bio-economic for rice straw fermented utilization as animal feed has been done through observation of the cattle biological parameter. An economic approach that has been used in the study was the partial budget analysis including the feed cost per gain (FC/g) and gross margin analysis. The results of the study has shown that FC/g of the cattle from Boyolali and Sumba Ongole (SO) were the most efficient in using the feed compared to the other four cattle. Those were Rp.4600,- and Rp.4995,- per head per day for cattle from Boyolali and SO, respectively. The two types of cattle also reached the gross margin estimation, however SO cattle was slightly less than that of the cattle from Boyolali (Rp.2854,- vs Rp.2897,- ) per head per day. The differences were very much depending on the growth rate of each type of the cattle. Â  Key words: Feed cost per gain, gross margin estimation, rice straw, beef cattle farming